Morphogenic Regulators Baby boom and Wuschel Improve Monocot Transformation. Issue 9 (6th September 2016) - Lowe, Keith; Wu, Emily; Wang, Ning; Hoerster, George; Hastings, Craig; Cho, Myeong-Je; Scelonge, Chris; Lenderts, Brian; Chamberlin, Mark; Cushatt, Josh; Wang, Lijuan; Ryan, Larisa; et al.
Abstract : Using the maize Bbm and Wus2 genes enhances transformation efficiency in maize and other monocots, broadens the genotype range, and permits transformation of mature seed-derived embryos and leaf segments. Abstract: While transformation of the major monocot crops is currently possible, the process typically remains confined to one or two genotypes per species, often with poor agronomics, and efficiencies that place these methods beyond the reach of most academic laboratories. Here, we report a transformation approach involving overexpression of the maize ( Zea mays ) Baby boom ( Bbm ) and maize Wuschel2 ( Wus2 ) genes, which produced high transformation frequencies in numerous previously nontransformable maize inbred lines. For example, the Pioneer inbred PHH5G is recalcitrant to biolistic and Agrobacterium tumefaciens transformation. However, when Bbm and Wus2 were expressed, transgenic calli were recovered from over 40% of the starting explants, with most producing healthy, fertile plants. Another limitation for many monocots is the intensive labor and greenhouse space required to supply immature embryos for transformation. This problem could be alleviated using alternative target tissues that could be supplied consistently with automated preparation. As a major step toward this objective, we transformed Bbm and Wus2 directly into either embryo slices from mature seed or leaf segments from seedlings in a variety of Pioneer inbred lines, routinely recovering healthy, fertile T0 plants. Finally, we demonstrated that the maize Bbm and Wus2 genes stimulate transformation in sorghum ( Sorghum bicolor ) immature embryos, sugarcane ( Saccharum officinarum ) callus, and indica rice ( Oryza sativa ssp indica ) callus.